2014
DOI: 10.1158/0008-5472.can-14-1450
|View full text |Cite
|
Sign up to set email alerts
|

Reducing CD73 Expression by IL1β-Programmed Th17 Cells Improves Immunotherapeutic Control of Tumors

Abstract: T helper (Th)-17 subsets hold promise in adoptive T cell transfer therapy for cancer. However, ex vivo programming of Th17 cells in presence of TGF-β increases cell surface expression of ectonucleotidases CD39 and CD73, that in turn increases susceptibility to immunosuppression and reduces effector functions. Our data shows that ATP mediated suppression of IFN-γ production by Th17 cells can be overcome either by genetic ablation of CD73 or by generating TGF-β independent Th17 in presence of IL-1β. Th17 cells c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 51 publications
5
41
0
Order By: Relevance
“…To merge the best functional traits of Th1 to Th17 cells, we modified the culture condition of Th17 IL1β+TGFβ cells (generated in presence of IL1β plus low dose of TGFβ), since they exhibited superior anti-tumor response as compared to conventional Th17 cells (generated in the presence of TGFβ) due to reduced ectonucleotidase expression (Chatterjee et al, 2014). We observed that combining the culture conditions of Th17 IL1β+TGFβ (IL6, IL1β, IL23, TGFβ lo ) and Th1 cells (with IL12) resulted in hybrid Th1/17 cells, which not only co-express elevated levels of IFNγ and IL17 (Figures 1A, S1A, and S1B) but also exhibit phenotypic signature akin to the pathogenic Th17 cells (Lee et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…To merge the best functional traits of Th1 to Th17 cells, we modified the culture condition of Th17 IL1β+TGFβ cells (generated in presence of IL1β plus low dose of TGFβ), since they exhibited superior anti-tumor response as compared to conventional Th17 cells (generated in the presence of TGFβ) due to reduced ectonucleotidase expression (Chatterjee et al, 2014). We observed that combining the culture conditions of Th17 IL1β+TGFβ (IL6, IL1β, IL23, TGFβ lo ) and Th1 cells (with IL12) resulted in hybrid Th1/17 cells, which not only co-express elevated levels of IFNγ and IL17 (Figures 1A, S1A, and S1B) but also exhibit phenotypic signature akin to the pathogenic Th17 cells (Lee et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that Th17 cells differentiated with low concentrations of TGFβ together with IL-6 and IL-1β express lower levels of CD73 and better antitumor activity 23 . LYC-54143 was assessed for its impact on CD73 expression under both differentiation conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The Kuchroo laboratory reported that IL-23-induced TGF-β3 promotes pathogenic Th17 cells in autoimmunity, as indicated by their gene expression of Tbx21 , RORC , ICOS , IL-23R , IL-7R and more [43]. How driving Th17 cells toward a regulatory versus pathogenic profile impacts their ability to kill tumors is under investigation, and the level and amount of certain cytokines have clearly been shown to impact their ability to survive, function and regress tumors in ACT models [38, 44, 45], as discussed later in this review.…”
Section: Introductionmentioning
confidence: 99%
“…Along with IL-12, it has been reported that the dose of TGF-β, IL-1β, IL-23 and IL-2 used to program CD4 + T cells to a Th17 phenotype can distinctly regulate their functional fate and capacity to regress tumors [38, 44, 45]. These findings underscore that small changes to cytokines, co-stimulation and pharmaceutical reagents in the Th17 culture can have unforeseen consequences in shaping memory responses to tumors.…”
Section: Introductionmentioning
confidence: 99%